Risk factors for radial artery calcification in patients with and without uremia - Jian-bing Hao; Si-yu Wang; Tong Chen; Bo Yuan; Li-rong Hao (BMC Nephrology)
Abstract Background Calcification of the radial artery is one of the main causes of anastomotic stenosis in autogenous arteriovenous fistulas in uremic patients. However, the pathogenesis of calcification is still unknown. This study attempted to screen and validate the risk factors for vascular calcification in patients with uremia. Methods Serum of blood were collected and tissue samples from radial artery were obtained from 60 uremia patients with or without hemodialysis. General biochemical indicators and calcification-related molecules were collected and detected via ELISA or correlation analysis. In addition, pathological changes and calcification-related molecules in the radial artery were evaluated by HE or immunohistochemical staining. Results There were differences in total calcium, calcium-phosphorus products, allograft inflammatory factor 1 (AIF-1), intact parathyroid hormone (iPTH), vitamin D (VD), fibroblast growth factor 23 (FGF23) and soluble klotho (sKlotho) in the blood of uremic patients with or without hemodialysis. Furthermore, these factors are related to calcification of the radial artery. The expression of AIF-1, PTHR1, VDR, FGF23 and sKlotho was also increased in the calcified radial artery. Conclusions The levels of AIF-1, PTH, VDR, FGF23 and sKlotho in serum were associated with calcification of the radial artery in patients with uremia. Furthermore, calcification of the radial artery was further aggravated by abnormalities in calcium and phosphorus in maintenance hemodialysis patients.